Rhizosphere microbiome engineering of Triticum aestivum L. - Shabana Wagi; Peer Schenk; Ambreen Ahmed; Eladl Eltanahay (Revista Brasileira de Ciência do Solo, 2023)
ABSTRACT Root-associated microbiomes (RAMs) are complex microbial communities, essential for plant growth and development. The RAMs interact with the roots, maintain the root architecture, protect plants from a plethora of pathogens and biotic and abiotic stress and intensify nutrient uptake, i.e., improve plant growth and yield. A wide variety of microbial populations is usually found in the rhizosphere. Plant exudates also play a significant role in the establishment of rhizospheric microbial communities. This study deals with the approach of microbiome engineering to enhance the development of crops such as wheat. We focus on the idea of soil engineering to foster beneficial microbial communities that can improve plant growth effectively and reduce competition by gradually decreasing the number of pathogenic communities. This technique enables plants to thrive under adequate edaphic conditions. In the current study, the rhizosphere of Triticum aestivum L. was analyzed over four generations. Variations in the microbial diversity between batches one to four (B1-B4) were analyzed with regard to their capacity to improve plant growth. Microbial species richness in the rhizosphere microbiome of wheat was recorded in all investigated plant batches (B0 to B4). The major phyla across the four plant batches were Proteobacteria, Chloroflexi and Actinobacteria. Jaccard Similarity Coefficient indicated similarity between the batches B4-treated and B4-control. Taxonomic distances between the bacterial communities of Batches B0, B1 and B4 were the highest. Significant improvements in the growth parameters of plants treated with a microbiome-containing soil solution of the previous generation (batch) were recorded. Subsequently, their microbiome was also engineered, which facilitated plant growth effectively.